Everyday understandings of drone incidents and misuse in the Mass Observation Archive. - Jackman, Anna (Geographical Journal, 2025)
Drones are a growing feature of everyday airspace, with more‐than‐military drones deployed across diverse civil, commercial, and recreational applications. Yet, from reports of drones flying in proximity to manned aircraft and transporting contraband into prisons to drones used to spy on ex‐partners, so too have concerns grown around drone incidents and misuse. Drawing on the testimony of Mass Observation Archive (MOA) correspondents, this article explores everyday understandings of drone incidents and misuse, while bringing drone geographies into novel dialogue with feminist geographical and geopolitical work on the everyday, storytelling, and (digital) technology. An established UK archival project, the MOA seeks the views of 'ordinary' people to inform an understanding of everyday life in Britain through issuing questionnaire‐style 'directives' on wide‐ranging themes, from current events to articles of interest, to its panel of volunteer correspondents. Drawing on the author's development of a drone‐themed directive, this article examines everyday understandings of growing and anticipated drone presence, while reflecting on the geopolitical implications of increasingly diffuse airpower as access to drones widens. In so doing, it responds to calls from drone geographies to diversify the methodologies deployed in the drone's critical accounting, while bringing the MOA dataset into dialogue with feminist work to deepen understandings of 'everyday droning'.